A CHEST-X RAY OVERVIEW OF COVID-19 PATIENTS IN BALI MANDARA HOSPITAL BETWEEN MARCH 2020 - AUGUST 2020 - Haryadi, Pande Made Doddy; Hermawan, I. P. G. (E-Jurnal Medika Udayana, 2021)
The primary examination of COVID-19 in China uses a Computed Tomography-Scan (CT-Scan). However, this CT-Scan examination has other drawbacks, namely the risk of transmission and not suitable for use in Indonesia. Another modality that can be used is Chest X-Ray (CXR) in examining COVID-19 and this already reviewed by the American College of Radiology. This study was conducted using a retrospective cross-sectional method of COVID-19 patients who were treated at BMH between March 2020 to August 2020, who had carried CXR examination to evaluate the results. 96 patients were recorded retrospectively who were admitted to BMH between March 2020 to August 2020. This group included 76 people with the age group 16 to 60 years and 20 people with age group over 60 years. On the patient CXR examination was found images with opacity 59 (61.5%); most lung opacity in the form of ground-glass turbidity 47 (79.7%) When classified according to Radiological Society of North America, the most appearance of pneumonia was found in the Typical Category (33 (55.9%)).Patients with COVID-19 may have certain feature of pneumonia on CXR examination. The findings of pneumonia on the CXR may help facilitate the initial diagnosis of suspected COVID-19 Keywords: COVID-19, CXR, Overview